Effects of feeder design on growth performance and carcass characteristics of finishing pigs - J R Bergstrom; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
Two experiments were conducted to compare the effects of feeder design (conventional dry vs. wet-dry feeder) on finishing pig performance. In Exp. 1, 1,186 pigs (PIC 337 × 1050) were used in a 69-d experiment. Pigs were weighed (avg. 70.8 lb) and allotted to 1 of 2 feeder types in a completely randomized design. There were 22 pens per feeder type with 26 to 28 pigs per pen. All pigs were fed the same dietary sequence in 4 phases (d 0 to 10, 10 to 28, 28 to 50, and 50 to 69). Overall (d 0 to 69), pigs using the wet-dry feeder had greater (P<0.001) ADG, ADFI, and final weight compared with pigs using the conventional dry feeder. In Exp. 2, 1,236 pigs (PIC 337 × 1050) were used in a 104-d experiment. Pigs were weighed (avg. 63.2 lb) and allotted to 1 of the 2 feeder types in a completely randomized design. There were 23 pens per feeder type with 25 to 28 pigs per pen. All pigs were fed the same feed budget (diet 1 = 59 lb/pig, diet 2 = 88 lb/pig, diet 3 = 121 lb/pig, and diet 4 = 130 lb/pig). On d 84, the 3 largest pigs per pen were marketed. Afterward, all remaining pigs were fed a fifth dietary phase containing Paylean until d 104. Carcass measurements were obtained after pigs were transported to a commercial abattoir on d 104. Overall (d 0 to 104), pigs using the wet-dry feeder had greater (P<0.001) ADG, ADFI, and final weight compared with those using the conventional dry feeder. However, pigs using the wet-dry feeder had poorer F/G and increased feed cost per pig (P<0.002) than pigs using the conventional dry feeder. Carcass yield, fat free lean index, premium per pig, and live value/cwt were increased, whereas average back fat depth was decreased (P<0.03) for pigs using the conventional dry feeder compared with pigs using the wet-dry feeder. The combination of these effects resulted in a numerically lower net income per pig for pigs fed with the wet-dry feeder. These experiments demonstrate that growth performance of finishing pigs was improved with a wet-dry feeder compared with a conventional dry feeder. However, because carcasses of pigs fed with a wet-dry feeder yielded less and were fatter, more research is required to understand the dynamics among feeder design, feed intake, and economic return.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Feeders; Pig